A Study of Experiments in Improving Science Literacy and Disciplinary Behavior of 6 Year-Old Children (Processing Organic Waste Using Black Soldier Fly Magot): (Processing Organic Waste Using Black Soldier Fly Magot) - Rakhmawati, Alkehfi; Puridawaty , Brigita (Kirana Publisher (KNPub), 2024)
Early childhood needs to process an understanding of natural phenomena and the world around them. Children are not yet aware of environmental problems because they are developing various skills such as science literacy skills and mindsets that are reflected in disciplinary attitudes. The purpose of the study was to determine the significance of increasing science literacy and disciplinary behavior of 6-year-old children by processing organic waste using black soldier fly maggots. The research method uses a quantitative approach through a quasi-experimental study process with the research from Nonequivalent Control Group Design. The results of theoretical research based on the comparison between the t count and t table show the t count of 3.792> 2.306, and the significant result is 0.001 <0.05, then Ha is accepted. So it is said that there is an increase in science literacy skills and disciplinary behavior of children aged 6 years, through organic waste processing experiments using black soldier fly maggot.